2020
DOI: 10.1124/dmd.120.090951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Erythromycin as a Tool to Assess CYP3A Contribution of Low Clearance Compounds in a Long-Term Hepatocyte Culture

Abstract: Long-term hepatocyte culture systems such as HepatoPac are well suited to evaluate the metabolic turnover of low clearance (CL) drugs because of their sustained metabolic capacity and longerterm viability. Erythromycin (ERY), a moderate, mechanism-based inhibitor of CYP3A, was evaluated as a tool in the HepatoPac model to assess contribution of CYP3A to the clearance of drug candidates. ERY inhibited CYP3A activity by 58% and 80% at 3 and 10 mM, respectively, for up to 72 hours. At 30 mM, ERY inhibited midazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Micropatterned co-cultures of human hepatocytes (from a male donor, 31 years of age) and mouse fibroblasts (HepatoPac®, BioIVT Inc.) were used to assess the metabolism of BI 425809 by CYP3A [ 12 ]. The co-cultures were received in a 96-well plate in maintenance media containing 10% foetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropatterned co-cultures of human hepatocytes (from a male donor, 31 years of age) and mouse fibroblasts (HepatoPac®, BioIVT Inc.) were used to assess the metabolism of BI 425809 by CYP3A [ 12 ]. The co-cultures were received in a 96-well plate in maintenance media containing 10% foetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 32 μl probing medium was added to each well of the 96-well plate, which was then placed into an incubator for 15 min in 10% carbon dioxide at 37 °C. [12]. Semi-quantitative data using the ratio of the peak area response of the analyte and internal standard (nevirapine for alprazolam and 13 C6-BI 425809) were used.…”
Section: Bi 425809 Metabolism By Human Hepatocytesmentioning
confidence: 99%
“… 59 The same company also showed that erythromycin, an inhibitor of CYP3A4, significantly inhibited in MPCCs the clearance of midazolam and alprazolam, two CYP3A4 substrates. 60 Finally, Vertex showed that drug-mediated induction of CYP2C enzymes was higher in MPCCs than in PHH monocultures; 61 furthermore, EC50 values (drug dose that causes 50% of maximal CYP induction) in MPCCs for rifampin-mediated CYP3A4 and CYP2C9 induction were more clinically relevant than monocultures, which was subsequently found to be due to higher uptake transporter activities in MPCCs that leads to more intracellular accumulation of drugs like rifampin than the monocultures, which were shown to have reduced transporter activities. 62 …”
Section: Engineered Human Liver Models Validated For Drug Testingmentioning
confidence: 99%
“…This demonstrated that FMO and CYP3A enzymes are important contributors to risdiplam metabolism and provided potential f m ranges for planning of a definitive in vivo DDI study. Since the time of performing these studies the first demonstrations of chemical inhibitor effectiveness and application to f m estimation using long-term hepatocyte cultures have started to emerge (Chan et al, 2020). These approaches will give additional opportunities for f m estimation, based upon total drug depletion, when such validation is available for a panel of selective inhibitors.…”
Section: Investigating the Combination Of Cyp P450 And Flavin-containing Monooxygenase Contributions To Risdiplam Metabolism And Implicatmentioning
confidence: 99%